2023
DOI: 10.3390/math11030663
|View full text |Cite
|
Sign up to set email alerts
|

Statistical and Ideal Convergences in Topology

Abstract: The notion of convergence wins its own important part in the branch of Topology. Convergences in metric spaces, topological spaces, fuzzy topological spaces, fuzzy metric spaces, partially ordered sets (in short, posets), and fuzzy ordered sets (in short, fosets) develop significant chapters that attract the interest of many studies. In particular, statistical and ideal convergences play their own important role in all these areas. A lot of studies have been devoted to these special convergences, and many resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Following the ideal in [8], Sun and Li [9] studied the B-topology on posets and found that the o-convergence in a poset P is topological if and only if the poset P is S * -doubly continuous, which demonstrates the equivalence between the o-convergence being topological and the S * -double continuity of a poset. Moreover, the ideal-o-convergence, a generalized form of o-convergence established via ideals, was defined in posets by Georgiou et al [10,11]. Also, the authors obtained that the ideal-o-convergence in a poset P is topological if and only if the poset P is S * -doubly continuous.…”
Section: Introductionmentioning
confidence: 99%
“…Following the ideal in [8], Sun and Li [9] studied the B-topology on posets and found that the o-convergence in a poset P is topological if and only if the poset P is S * -doubly continuous, which demonstrates the equivalence between the o-convergence being topological and the S * -double continuity of a poset. Moreover, the ideal-o-convergence, a generalized form of o-convergence established via ideals, was defined in posets by Georgiou et al [10,11]. Also, the authors obtained that the ideal-o-convergence in a poset P is topological if and only if the poset P is S * -doubly continuous.…”
Section: Introductionmentioning
confidence: 99%